مستوى توظيف العاب الكمبيوتر التربوية في تنفيذ الأنشطة التربوية برياض الأطفال والصعوبات التي تواجه معلمات رياض الأطفال في تصميمها وتوظيفها من وجهة نظرهن - دويكأ. سنيه مصطفى حسن (Aljameai, 2025)
المستخلص: هدف هذا البحث إلى التعرف على مستوى توظيف العاب الكمبيوتر التربوية في الأنشطة التربوية برياض الأطفال ومعرفة الصعوبات التي تواجه المعلمات في تصميمها وتوظيفها من وجهة نظرهن ، ولتحقيق أهداف البحث تم استخدام المنهج الوصفي ، وتكونت عينة البحث من معلمات رياض الأطفال بمراقبة تعليم سوق الجمعة وعددهم63 معلمة ، وتم استخدام أداة الاستبانة من إعداد الباحثة لجمع البيانات ، وأظهرت النتائج أن مستوى توظيف العاب الكمبيوتر التربوية في تنفيذ الأنشطة التربوية برياض الأطفال هو مستوى مرتفع ، وتواجه معلمات رياض الأطفال صعوبات في تصميم وتوظيف العاب الكمبيوتر التربوية في الأنشطة منها صعوبات مادية وفنيه . ولم يختلف مستوى توظيف العاب الكمبيوتر التربوية في تنفيذ الأنشطة التربوية برياض الأطفال حسب متغيرات: (المؤهل، سنوات الخبرة) ، كذلك لم يختلف مستوى الصعوبات التي تواجه معلمات رياض الأطفال في تصميم وتوظيف العاب الكمبيوتر التربوية في الأنشطة حسب المتغيرات (المؤهل العلمي، سنوات الخبرة). Abstract This research aimed to identify the level of employment of educational computer games in educational activities in kindergartens and to know the difficulties faced by teachers in designing and employing them from their point of view. To achieve the research objectives, the descriptive approach was used, and the research sample consisted of kindergarten teachers in the Souq Al-Jumaa Education Supervision, numbering 63 teachers. A questionnaire prepared by the researcher was used to collect data. The results showed that the level of employment of educational computer games in implementing educational activities in kindergartens is high, and kindergarten teachers face difficulties in designing and employing educational computer games in activities, including financial and technical difficulties. The level of employment of educational computer games in implementing educational activities in kindergartens did not differ according to the variables: (qualification, years of experience). Likewise, the level of difficulties faced by kindergarten teachers in designing and employing educational computer games in activities did not differ according to the variables (academic